Smart grid wireless communications: a cyber-physical system perspective. (29th July 2021) - Fu, Ruxiang; Zhang, Jiawei; Zhang, Yu; Wang, Xudong
It is widely accepted that wireless communications play an important role in smart grid. However, wireless communication usually lacks sufficient quality, security, and reliability that are critically demanded by power grid. Thus, it is indispensable to study the applicability of wireless communications for smart grid. In this paper, interactions between a wireless communication network and smart grid are characterised from the perspective of a cyber-physical system (CPS). Based on this CPS framework, integration of smart grid and wireless networks is categorised into two scenarios: loosely-coupled CPS and tightly-coupled CPS. The features of both scenarios are discussed and compared, which leads to clear guidelines on the design of a smart grid wireless communication system. To concretely demonstrate these guidelines, two examples are presented to show different roles of wireless communications in loosely-coupled CPS and tightly-coupled CPS. Following these examples, remaining research challenges and potential solutions are discussed.